Pengembangan Web Perpustakaan Digital Berbasis PHP dan Bootstrap Untuk Meningkatkan Akses Informasi Koleksi Buku - Dharmabuddha, I Kadek Andika; Aryantini, Ni Putu Candra; Suarningsih, Ni Wayan; Pradnyadewi, Anak Agung Istri Bintang; Sentosa, I Kadek Edho Teguh; Sanjaya, I Gede Wahyu (Journal Informatics Nivedita, 2025)
This research is designed to build a web-based digital library system by utilizing the PHP programming language, Bootstrap framework, and MySQL database. This system is developed as a solution for small to medium educational institutions in providing organized, efficient, and easily accessible library services. The methodology used is Research and Development (R&D) with a Waterfall model approach, which contains the stages of needs analysis, design, implementation, testing, and evaluation. System features include book data management, student information, loan transactions, and keyword-based searches. This test uses the black box testing method and shows full validation results for all features. The results of the study show that the system runs as expected and has a responsive and easy-to-use interface. This system is expected to support the library digitization process and increase access to book information optimally.